STRATEGI PENGEMBANGAN PRODUK PEMBIAYAAN MUSYARAKAH DI KJKS BAITUL MAAL WA TAMWIL (BMT) AGAM MADANI NAGARI KOTO TUO, KECAMATAN IV KOTO, KABUPATEN AGAM - Irvan Habib; Iiz Izmuddin (Program Studi Ekonomi Islam - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
This research is motivated by the development of Islamic financial institutions in Indonesia, which has driven innovation in financing products, one of which is financing under the musyarakah contract. However, in practice, Islamic microfinance institutions such as KJKS BMT Agam Madani face various challenges in developing these products, particularly following the COVID-19 pandemic, which has impacted the business continuity of MSEs. This study aims to determine the musyarakah financing product development strategy implemented by KJKS BMT Agam Madani and the obstacles encountered in this process. The research method used is a qualitative approach with descriptive methods. The data used are primary and secondary. Primary data were obtained directly from respondents through in-depth interviews and observation. Secondary data were collected from KJKS BMT Agam Madani's financial reports and supporting academic literature. Data collection techniques were conducted through interviews, observation, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The research instruments were managers and employees of KJKS BMT Agam Madani, as well as customers (MSEs) in Nagari Koto Tuo. The research results indicate that product development strategies are implemented through adjustments to product characteristics, classification of the types of businesses financed, and implementation of marketing strategies such as outreach, training, and visual promotion. However, the development of musyarakah products faces obstacles such as declining purchasing power, high business risks, and limited capital due to customer withdrawals. This study recommends the importance of regular product evaluation, business mentoring, and strengthening risk mitigation strategies as part of efforts to strengthen musyarakah financing and support the sustainability of micro-enterprises.